THE ROLE OF FIRST LANGUAGE IN EFL CLASSROOM - Faishal Zakaria (Jurnal Ilmiah Didaktika, 2013)
This paper gives an overview of some of basic arguments of the use of L1 in L2 classroom, either against or in favor of it, and will particularly review the use of L1 in classroom of EFL adult learners in Indonesia. Despite to opponent arguments of L1 use, there are a number of proponent arguments from ESL/EFL professionals of its use. They argue that L1 use is beneficial for both teacher and student if it isused appropriately at appropriate times. The use of L1 in classroom is particularly helpful for teacher when helping engender security, conveying meaning of words, checking for comprehension, and or explaining grammatical rules.